Unit Produksi dan Jasa sebagai Edupreneurship - Desy Anggreani; Sudarmiatin Sudarmiatin; Suharto Suharto (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This study focuses on identifying internal and external factors from Crystal Guava Production and Service Unit of SMK 2 Batu. Therefore, strategies for the development of Production Units as edupreneurship can be obtained, namely vehicles for practicing work and entrepreneurship for students by doing creative and innovative efforts, the use of technology at the time of the guava crystal production process and its marketing implementation. Based on the internal factor analysis of the UPJ in SMK 2 Batu at 1.19 and the external factor analysis of 1.15 which is then analyzed using the SWOT matrix at the coordinate point (1.19:1.15) which means the quadrant I (SO) namely having to develop their internal power be`1cause the opportunity to develop UPJ in SMK N 2 batu is widely opened. The SO strategy that has been developed based on the SWOT matrix is (1) making Guidelines for production activities of Production Units that propose Curriculum, (2) product development and the use of the latest technology in organic crystal cultivation, (3) expanding market share with promotional media on social media, (4) increasing student involvement in cultivation and marketing (sales services, promotion in social media), (5) increasing collaboration with industrial parties to transfer knowledge and technology of crystal guava cultivation and maintain continuity of guava products.Abstrak: Penelitian ini berfokus untuk mengindentifikasi faktor internal dan faktor eksternal dari Unit Produksi dan Jasa Jambu Kristal SMKN 2 Batu sehingga diperoleh strategi-strategi pengembangan Unit Produksi sebagai Edupreneurship yaitu wahana berlatih bekerja dan berwirausaha bagi siswa dengan melakukan yang usaha kreatif dan inovatif, dan penggunaan teknologi pada saat budidadaya Jambu Kristal serta pemasarannya. Berdasarkan analisis faktor internal dari Unit Produksi dan Jasa SMKN 2 Batu sebesar 1,19 dan analisis faktor eksternal sebesar 1,15 yang selanjutnya dianalisis susuai matriks SWOT berada pada titik koordinat (1,19: 1,15) yang berarti pada kuadran I (SO) yaitu harus mengembangkan kekutan internalnya karena peluang untuk mengembangkan Unit Produksi dan Jasa SMKN 2 Batu sebagai Edupreneurship terbuka lebar. Adapun strategi SO yang dikembangkan. Adapun strategi SO yang telah dikembangkan berdasarkan matriks SWOT ialah (1) pembuatan Pedoman kegiatan produksi Unit Produksi yang mengaju Kurikulum, (2) melakukan pengembangan produk dan penggunaan teknologi terbaru pada budidaya jambu kristal (organic), (3) memperluas pangsa pasar dengan media promosi di media sosial, (4) peningkatan keterlibatan siswa dalam budidaya dan pemasaran (layanan penjualan, promosi di media soasial), (5) Meningkatkan kerjasama dengan pihak DU/DI yang sejenis untuk transfer ilmu dan teknologi budidaya jambu kristal dan menjaga kontinuitas produk jambu.